Microscopic investigations of surface texture of siloxane‐hydrogel contact lenses. (15th February 2019) - Stach, Sebastian; Ţălu, Ştefan; Głuchaczka, Alicja; Siek, Patrycja; Zając, Joanna; Tavazzi, Silvia
Abstract : Purpose: The objective of this article was to investigate experimentally the 3‐D surface of unworn/worn contact lenses (CLs) using stereometric analysis applied to atomic force microscopy (AFM) micrographs. Materials and methods: Fractal and stereometric analyses were applied in micromorphology investigations of siloxane‐hydrogel CLs made of Filcon V. Qualitative and quantitative study of surface texture was made using statistical parameters of 3‐D surface roughness, according with ISO 25178‐2: 2012 for: CLrins (unworn CLs taken from the blister and rinsed with deionized water); CLworn‐smooth (worn for 8 h and presenting a smooth‐type morphology), and CLworn‐sharp (worn for 8 h and presenting a sharp‐type morphology). Results: Fractal analysis reveals fractal nature at nanometer scale of all surface samples. The fractal dimensions determined by enclosing boxes method of the studied samples are: D f = 2.25 ± 0.01 for CLrins, D f = 2.29 ± 0.01 for CLworn‐smooth and D f = 2.40 ± 0.01 for CLworn‐sharp . Conclusions: Surface statistical parameters can be deduced by analyses of micromorphology and fractal structure of the 3‐D surface of CLs. The variation of these parameters provides quantitative information on the effects of wear, such as in the cases of the two morphologies which can be found after 8 h wear of Filcon V CLs. POLYM. ENG. SCI., 59:E442–E451, 2019. © 2019 Society of Plastics Engineers